2020
DOI: 10.1016/j.cemconres.2020.106014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of long term weathering on hemp and rapeseed concrete

Abstract: Two vegetal aggregate types are studied for their performance regarding immersion and outdoor weathering. The most widely researched bio-aggregate to date is hemp shiv; which is used in this study as well as chopped rapeseed straw which is an alternative bio-aggregate widely available in the UK. In this study the binder used is Vicat prompt natural cement as well as a viscosity modifying agent (VMA) admixture. It was found that the hemp aggregate produced the most durable concrete when compared to rapeseed, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…It can be observed that the addition of VMA demonstrates significant improvement of compression strength at 7 d and 28 d of both mixes for shattered wall and roof. These results confirm the benefit of using VMA where the quality of the ITZ improved and the porosity of the matrix overall is reduced which led to an increase in the compressive strength (Sheridan et al, 2020).…”
Section: Compression Strength At 5% Of Deformationsupporting
confidence: 75%
See 1 more Smart Citation
“…It can be observed that the addition of VMA demonstrates significant improvement of compression strength at 7 d and 28 d of both mixes for shattered wall and roof. These results confirm the benefit of using VMA where the quality of the ITZ improved and the porosity of the matrix overall is reduced which led to an increase in the compressive strength (Sheridan et al, 2020).…”
Section: Compression Strength At 5% Of Deformationsupporting
confidence: 75%
“…Vegetal concrete, a bio-based building material, has emerged as a sustainable material that provides excellent levels of insulation, leading to huge energy saves (Sheridan et al, 2020). Hemp concrete has a low dry density ranging between 200 and 800 kg/m 3 , making it a lightweight composite insulating material (Nozahic and Amziane, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have highlighted that plant fibre-reinforced cement composites are vulnerable to weathering and water absorption [68,69]. Therefore, the water absorption of bio-based cement composites is an important parameter for the durability of this material.…”
Section: Capillary Water Absorptionmentioning
confidence: 99%
“…Concrete-based composites are mostly subject to environmental effects that lead to their deterioration, such as chemical attacks (e.g., chloride [124], acid [125], etc. ), physical weathering [126], and temperature [127], among others. The reinforcements employed in these structures exhibits versatility, manifesting in either metallic forms such as steel or high-strength alloys or in the form of fibre-reinforced polymers (FRPs) incorporating glass, carbon, or basalt fibres.…”
Section: Aging Of Cement-based Materialsmentioning
confidence: 99%